SOLUTION OF NONLINEAR FRACTIONAL BOUNDARY VALUE PROBLEMS WITH NONHOMOGENEOUS BOUNDARY CONDITIONS - Alkan, S.; Secer, A. (MINISTRY COMMUNICATIONS & HIGH TECHNOLOGIES REPUBLIC AZERBAIJAN, 2015)
In this paper, as an original contribution to literature, sinc-collocation method is firstly presented to solve the nonlinear fractional boundary value problem with nonhomogeneous conditions. Obtained results are given as two new theorems. To illustrate the efficiency and robustness of the introduced method some numerical examples are presented.
Keywords: Nonlinear Boundary Value Problems; Sinc-Collocation Method; Caputo Derivative; Nonhomogeneous Boundary Conditions; ADOMIAN DECOMPOSITION METHOD; HOMOTOPY PERTURBATION METHOD; KDV-BURGERS EQUATION; DIFFERENTIAL-EQUATIONS; GALERKIN METHOD; NUMERICAL-SOLUTION; ORDER; Mathematics